2020
DOI: 10.3390/ijms21010327
|View full text |Cite
|
Sign up to set email alerts
|

Disabling the Protease DDI2 Attenuates the Transcriptional Activity of NRF1 and Potentiates Proteasome Inhibitor Cytotoxicity

Abstract: Proteasome inhibition is used therapeutically to induce proteotoxic stress and trigger apoptosis in cancer cells that are highly dependent on the proteasome. As a mechanism of resistance, inhibition of the cellular proteasome induces the synthesis of new, uninhibited proteasomes to restore proteasome activity and relieve proteotoxic stress in the cell, thus evading apoptosis. This evolutionarily conserved compensatory mechanism is referred to as the proteasome-bounce back response and is orchestrated in mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Our results imply that non-viral retroviral-like PRs potentially have relatively lower dimer stability compared to retroviral counterparts. We assume that getting better insight into the structural requirements for the dimer formation through the protease domain may help understanding the roles of Ddi-like proteins in proteasomal shuttles and ubiquitination pathways [6,7,63,64,67,68,84,85], even in physiological or pathological conditions. Furthermore, future studies are needed to prove our findings by determining the in vitro dimer stabilities, and correlating the features described in our study with those of additional eukaryotic retroviral-like or endogenous retrovirus PRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results imply that non-viral retroviral-like PRs potentially have relatively lower dimer stability compared to retroviral counterparts. We assume that getting better insight into the structural requirements for the dimer formation through the protease domain may help understanding the roles of Ddi-like proteins in proteasomal shuttles and ubiquitination pathways [6,7,63,64,67,68,84,85], even in physiological or pathological conditions. Furthermore, future studies are needed to prove our findings by determining the in vitro dimer stabilities, and correlating the features described in our study with those of additional eukaryotic retroviral-like or endogenous retrovirus PRs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Ddi1-Sc PR provided evidence for its proteolytic activity, which was found to be required for sufficient checkpoint regulation [61] and to contribute to protein secretion [62], DNA replication stress response [63], and DNA-protein crosslink repair [64]. In Caenorhabditis elegans, Ddi1 expression was found to be induced by proteasome dysfunction; furthermore, results proved that the catalytic activity of Ddi1 PR is necessary for protein activation [65], and involvement of PR activity in Nrf1 processing was also demonstrated for human Ddi2 PR [66,67]. Protease domain of Ddi1-Hs protein was found to undergo post-translational modification, ubiquitination sites were identified in the proximities of the active site (K192) and the dimer interface (K382) [68], but effect of these modifications of protease function has not been elucidated.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent study shows that Nrf1 is cleaved by the DNA damage-inducible 1 homolog 2 (DDI2) protease, resulting in the release of a proteolytic fragment of Nrf1 from the ER into the nucleus, activating the transcription of proteasome subunit genes. Recently, it was shown that DDI2-deficient or protease-dead DDI2 mutant MDA-MB231 human breast adenocarcinoma cells are more sensitive to carfilzomib-induced apoptosis [85], suggesting that DDI2 is significant to the bounce-back response.…”
Section: Retrotranslocation From the Er And Proteolytic Processing Armentioning
confidence: 99%
“…However, Nrf1 processing occurs in the absence of S1P, S2P, ER membrane-resident rhomboid proteases, or the proteasome. Notably, it was recently shown that Nrf1 is able to enter the nucleus without cleavage [85]. Therefore, the Nrf1 activation mechanism was considered to be resulting from a non-canonical pathway; as such, its precise mechanism remains unknown ( Figure 4).…”
Section: Retrotranslocation From the Er And Proteolytic Processing Armentioning
confidence: 99%